2004
DOI: 10.1073/pnas.0307185101
|View full text |Cite
|
Sign up to set email alerts
|

Sensory neuron-specific receptor activation elicits central and peripheral nociceptive effects in rats

Abstract: The sensory neuron-specific G protein coupled receptors (SNSRs) have been described as a family of receptors whose expression in small diameter sensory neurons in the trigeminal and dorsal root ganglia suggests an implication in nociception. To date, the physiological function(s) of SNSRs remain unknown. Hence, the aim of the present study was to determine the effects of rat SNSR1 activation on nociception in rats. The pharmacological characterization of rat SNSR1 was initially performed in vitro to identify a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
93
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(101 citation statements)
references
References 23 publications
4
93
1
Order By: Relevance
“…Regarding the MRGPR-X1 subtype, one rodent receptor activated by BAM8 -22 was identified in mice and rats (MRGPR-C) (1, 2). However, apart from common high affinity binding to BAM8 -22, rodent MRGPR-C and human MRGPR-X1 exhibit fundamental differences in their affinity to other endogenous peptides, as previously reported (4,52,53). Furthermore, in contrast to rodent MRGPR-C, human MRGPR-X1 resist ␤-arrestin-dependent, agonist-promoted endocytosis (4), not only affecting signal duration but also directing GPCR-promoted signaling toward distinct signaling pathways (54).…”
Section: Discussionmentioning
confidence: 89%
“…Regarding the MRGPR-X1 subtype, one rodent receptor activated by BAM8 -22 was identified in mice and rats (MRGPR-C) (1, 2). However, apart from common high affinity binding to BAM8 -22, rodent MRGPR-C and human MRGPR-X1 exhibit fundamental differences in their affinity to other endogenous peptides, as previously reported (4,52,53). Furthermore, in contrast to rodent MRGPR-C, human MRGPR-X1 resist ␤-arrestin-dependent, agonist-promoted endocytosis (4), not only affecting signal duration but also directing GPCR-promoted signaling toward distinct signaling pathways (54).…”
Section: Discussionmentioning
confidence: 89%
“…In addition, the RF-amides increase peripheral pain responses consistent with nociceptor modulation (29). Some of these molecules may stimulate nociceptors by interacting with acid-sensing ion channels (30), but the algogenic effect of RF-amides in rats, was not inhibited by pharmacological blockers of acid-sensing ion channels.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, that rodents (MrgA-H) and humans (MrgD, MrgX) contain more than one Mrg, which may form heterodimers, suggests that the readouts from painful stimuli mediated by Mrgs may be complex. In vivo evidence for Mrgs in pain is limited, but one report found that activation of SNSR1 (MrgC) by its ligand, ␥2-MSH, was pronociceptive (Grazzini et al, 2004). Finally, a change in MrgD levels in response to chronicconstriction injury, a model of inflammatory and neuropathic pain, was noted by Shinohara et al (2004), but an increase or decrease in MrgD levels was not reported.…”
Section: Discussionmentioning
confidence: 99%